Padrões e fatores associados à limitação de atividade e restrição à participação em pessoas acometidas por hanseníase no período de 2001-2014 em Picos/PI - Nascimento, Danelle da Silva (2019)
Leprosy, a neglected and infectious disease of chronic evolution, due to the involvement of peripheral nerves, keeps contributing to the development of disabilities and deformities, which can affect the routine of daily activities and deformities, which can affect the routine of daily activities and different aspects of social life of affected people. This study aimed to characterize clinical and demographic patterns and factors associated with limitation of activity, restriction and participation of people affected by leprosy, in the municipality of Picos - PI, from 2 - sectional study with descriptive and analytical approach, linked to the macroproject of operational research IntegraHans Piauí. Participants answered the sociodemographic questionnaires and underwent a simplified neurological evaluation, in addition to the application of the SALSA scale (activity limitation) and Participation scale (participation restriction). Data analysis was performed from the Stata version 11.0 program by univariate and bivariate analyzes with the calculation of the prevalence ratio and its 95% confidence interval and the Pearson chi square test and Fisher exact test and linear correlation, with a significance level of 0.05% adopted. A total of 263 people were identified, with the following profile: male (50.2%), 60 years of age or older (36.9%), incomplete elementary school (43.0%), brown skinned (50.6%), urban (94.3%), economically active (44.1%), married or in a stable union (57.0%), with less than 1 minimum wage (71.5%), with access to water (94.3%), garbage collection (84.0%), multibacillary operational classification (52.5%), prevalence of physical disability 1 at the present moment (59.3%) and with occurrence of reactional episodes according to medical records (42.6%). It was also observed that 119 (45.3%) had some degree of activity limitation and 63 (24%) some degree of restriction to participation. There was statistically significant associations between activity limitation, disability (RP: 1.66, CI: 1.14-2.41, p <0.01), age from 60 years (RP: 1.68, CI:1.09-3,02, p:0.043), low schooling (RP: 1.76, CI: 1.26-2.45, p <0.01) as risk fac-tors and the association between activity limitation and marital status as a protection factor, being verified both among single (RP: 0.57, 95% CI: 0.38-0.87, p:0.023) and married (RP: 0.72, 95% CI 0.54-0.96, p:0.023). There was also an association and between restriction, degree of disability (RP: 1.39; CI: 0.98-1.98; p:0.046) and operational classification (RP: 1.78; CI: 0.98-3.21; p:0.043). There was a significant correlation between EHF score and activity limitation (r = 0.2880, p <0.01), EHF score and participation restriction (r = 0.2678 and p <0.01) and activity limitation and restriction in individuals multibacillary (r = 0.5413, p <0.01). The activity limitation was more recurrent than the participation restriction. The verified associations refer us to the question of vulnerability being present and demonstrates influence on the conditions of transcendence and chronicity of the disease, reaffirming the need for longitudinal and multiprofessional follow-up, from the timely diagnosis to the post-discharge period. The SALSA and participation of people affected by leprosy, allowing the health professional to guide their assistance beyond the physical aspects and approach issues related to the person's life situations, to know the areas most affected in related to the limitation of activity and the restriction of participation, being able to provide a more individualized assistance, in the perspective of integrality and allowing to conduct the actions of confrontation in intersectorial areas and in the health sector.